Social Loafing and Team Development: A Barrier to Achieving UNESCO's Sustainable Development Goals - Susan, Kemigisha (Advances in Social Sciences Research Journal, 2025)
This qualitative study examines the phenomenon of social loafing in team settings, exploring its impact on team development and strategies to mitigate its effects. Through a comparative analysis of three case studies of multinational corporations, this study identifies key factors that contribute to social loafing and its consequences on team performance. The findings highlight the significance of leadership, clear goal-setting, and regular feedback in promoting a culture of accountability and motivation. This research contributes to the existing literature on social loafing and team development, providing valuable insights for organizations and teams seeking to promote collaboration, productivity, and social justice. The study’s results have implications for leadership development, team management, and organizational performance, emphasizing the need for intentional strategies to mitigate social loafing and foster effective teamwork.